Learning Android Studio - Stanley, Chris (Infinite Skills, 2015)
"In this Learning Android Studio training course, expert author Chris Stanley will teach you how to use Android Studio to develop on the Android platform. This course is designed for the absolute beginner, meaning no previous experience with Android Studio is required. You will start by learning about basic project configuration and configuration settings, including code style settings, inspections, and debugging. From there, Chris will teach you how to work with Android activities, navigate Android Studio, and debug. This video tutorial also covers how to optimize code, configure Android virtual devices, and refactor. Finally, you will learn about APK signing. Once you have completed this computer based training course, you will be fully capable of developing in Android Studio."--Resource description page.